Pembelajaran Karakteristik Grafik Fungsi dan Perubahannya Akibat Transformasi F^2 (X), 1/(F(x)), Dan |F(x)| Menggunakan Geogebra - Rizka Azizatul Latifah (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
The 21st century skills or 4C skills (critical thinking and problem solving, communication, collaboration, creative and innovative) are highly needed to thrive in the era of the fourth industrial revolution. These skills can be developed through learning, and it is important to incorporate them into the learning process, including mathematics education. Analyzing activities can be a way to sharpen students' thinking skills. One of the topics that requires analysis is the characteristics of function graphs and their changes due to transformations. The purpose of this article is to explain how to teach the characteristics of functions and their changes due to transformations of , , and using Geogebra, and its correlation with the improvement of 4C skills. The method used in this article is literature review. In analyzing function graphs, it is necessary to have learning media that can facilitate the learning process. One suitable media for learning function graphs is Geogebra, a software that can visualize mathematical objects such as function graphs. Using Geogebra in learning can sharpen critical thinking skills, creative thinking skills, collaboration skill, and communication skill.